2022
DOI: 10.3389/fnhum.2022.945406
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of eye movement during rapid automatized naming

Abstract: Numerous studies have focused on the understanding of rapid automatized naming (RAN), which can be applied to predict reading abilities and developmental dyslexia in children. Eye tracking technique, characterizing the essential ocular activities, might have the feasibility to reveal the visual and cognitive features of RAN. However, traditional measures of eye movements ignore many dynamical details about the visual and cognitive processing of RAN, and are usually associated with the duration of time spent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Additionally, due to the inherent nonlinear properties in gaze time‐series during RJA (as illustrated in this study), it is natural to employ a nonlinear time‐series analysis to improve the measurement sensitivity. For instance, our group recently showed that an entropy‐based method was more sensitive to reflect small perturbation of eye movements than traditional metrics (Wang et al, 2022). However, as far as we know, it has not been deeply investigated nonlinear features of gaze time‐series during RJA in children with ASD (de Belen et al, 2023; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, due to the inherent nonlinear properties in gaze time‐series during RJA (as illustrated in this study), it is natural to employ a nonlinear time‐series analysis to improve the measurement sensitivity. For instance, our group recently showed that an entropy‐based method was more sensitive to reflect small perturbation of eye movements than traditional metrics (Wang et al, 2022). However, as far as we know, it has not been deeply investigated nonlinear features of gaze time‐series during RJA in children with ASD (de Belen et al, 2023; Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We employed a Chinese adaptation of RAN (C-RAN) ( 27 ) that substituted highly-frequently-used Chinese characters for English letters. The C-RAN paradigm in this study consisted of four tasks: Task N-number (i.e., naming of numbers), Task N-character (i.e., naming of Chinese characters), Task N-object (i.e., naming of objects), and Task N-color (i.e., naming of colors).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, it can be utilized to monitor the focus locations sequentially and document the critical ocular activities during RAN. Even though several studies (Jones et al, 2008(Jones et al, , 2016Kuperman and Van Dyke, 2011;Pan et al, 2013;Hogan-Brown et al, 2014;Gordon and Hoedemaker, 2016;Kuperman et al, 2016;Silva et al, 2016;Nayar et al, 2018Nayar et al, , 2021Akhand et al, 2019;Araújo et al, 2021;Wang et al, 2022) have explored the characteristics of gaze behavior during RAN, only a few of them have ever examined whether and how gender, age, and task type alter these characteristics simultaneously. Additionally, researchers have not fully explored gaze behavior during a Chinese adaptation of RAN in order to broaden the application of RAN to developmental dyslexia in Chinese.…”
mentioning
confidence: 99%
“…Recent studies (Constantino et al, 2017;Del Bianco et al, 2021;Hedger and Chakrabarti, 2021;Nayar et al, 2022) proposed the idea of treating the eye-tracking data as a time series, allowing us to track the moment-by-moment changes in gaze behavior during cognitive tasks. Although this idea has been hailed as a significant advancement in eye-tracking analysis, it has not yet been thoroughly examined in the context of RAN (Wang et al, 2022). Additionally, the performance would be further enhanced if a more potent time series analysis technique can be adopted from the perspective of non-linear dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation